1996
DOI: 10.1007/bf01808159
|View full text |Cite
|
Sign up to set email alerts
|

Response ofBacillus subtilis spores to dehydration and UV irradiation at extremely low temperatures

Abstract: Spores of Bacillus subtilis have been exposed to the conditions of extreme dehydration (argon/silica gel; simulated space vacuum) for up to 12 weeks at 298 K and 80 K in the dark. The inactivation has been correlated with the production of DNA-double strand-breaks. The temperature-dependence of the rate constants for inactivation or production of DNA-double strand-breaks is surprisingly low. Controls kept in the frozen state at 250 K for the same period of time showed no sign of deterioration. In another serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…In many terrestrial microorganisms the detrimental effects of UV radiation may be synergistically increased by extremes such as desiccation and reduced atmospheric pressure (Lindberg and Horneck 1991, Dose et al 1991, Horneck 1993, Dose and Klein 1996. On the surface of Mars the existence of oxidants in the upper layers of the martian regolith (e.g., Hunten 1979) would also be a significant additional stress to a putative surface biota.…”
Section: Uv Radiation On An Environmentally Deteriorating Marsmentioning
confidence: 98%
See 2 more Smart Citations
“…In many terrestrial microorganisms the detrimental effects of UV radiation may be synergistically increased by extremes such as desiccation and reduced atmospheric pressure (Lindberg and Horneck 1991, Dose et al 1991, Horneck 1993, Dose and Klein 1996. On the surface of Mars the existence of oxidants in the upper layers of the martian regolith (e.g., Hunten 1979) would also be a significant additional stress to a putative surface biota.…”
Section: Uv Radiation On An Environmentally Deteriorating Marsmentioning
confidence: 98%
“…Recent data have been gathered on the effects of UV radiation on Bacillus subtilis spores exposed to vacuum and dehydration (Horneck 1993, Dose andKlein 1996). Bacillus subtilis is a good model for the examination of planetary protection issues since studies on the microbiological profile of the Viking landers (Puleo et al 1977) showed that Bacillus spp.…”
Section: Uv Radiation On Present-day Mars-biological Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposure of spores of B. subtilis and cells of D. radiodurans to extended periods of vacuum (3 × 10 −4 Pa) resulted in DNA strand breaks and crosslinking of DNA to proteins (Dose et al 1991, Dose andGill 1995). At low temperatures (e.g., 80 K) the rate constants for production of DNA strand breaks were reduced by approximately a factor of 2 compared to room temperature (Dose and Klein 1996). Unique tandem-base change mutations were observed in B. subtilis spores after forced dehydration of its DNA in vacuum of 10 −5 Pa (Munakata et al 1997).…”
Section: Threats To Dna By Oxygen Hydrolysis Other Chemicals Vacuumentioning
confidence: 98%
“…Important from an experimental point view, therefore, is the study of survival of terrestrial organisms under simulated extraterrestrial conditions and various conditions of stress [2]. For example, following this experimental approach, the survival of bacterial spores (e.g., Bacillus spores) under simulated martian environmental conditions (SMEC) has been reported [3,4] as well as their survival under extreme conditions of ultraviolet radiation [5,6], heavy ions [7], simulated Mars solar radiation [8][9][10][11], low-pressure plasma [12], microgravity [13], outer space [14,15], Martian atmospheric pressure and composition [16], space vacuum and ultraviolet irradiation [17], and the comparative effects of several stresses on vegetative cells and spores [18] as well as under the environmental conditions of Jupiter's moon, Europe [19]. Survival of other bacteria, including an acidophilic chemolithotroph isolated from the Rio Tinto (Spain) and belonging to the Acidithiobacillus genus and Deinococcus radiodurans has been studied under SMEC [20], as well as methanogens under conditions of extreme dryness [21].…”
Section: Introductionmentioning
confidence: 99%